The effects of the nurse work environment on job satisfaction, safety atmosphere, and reasons for missing care: cross-sectional research - Kholod khatem Almutairi; Halah Abdullah Alanazi; Hanan Debshi Alanazi; Razan rashed dafer alshehri; Khalid Ahmed Alshehri; Mansour Marzouq alotaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The nursing work environment significantly impacts patient safety, job satisfaction, and the occurrence of missed care, all of which contribute to the quality of healthcare services. In public teaching hospitals, nurses frequently face challenges, such as inadequate staffing, limited resources, and poor nurse-physician collaboration. This study aims to examine how organizational factors within the nursing work environment influence missed nursing care, safety climate, and job satisfaction among nursing professionals. Methods: This cross-sectional study included 219 nurses and nurse technicians working in adult medical/surgical and critical care units at public teaching hospitals. Data were collected through the Practice Environment Scale (PES), the Miss care survey, and selected items from the Safety Attitudes Questionnaire (SAQ). Based on PES subscale scores, work environments were categorized as "good," "mixed," or "poor" to analyze the relationship between these categories and reported levels of missed care, job satisfaction, and perceptions of safety climate. Results: The analysis revealed that nurses working in environments classified as "good" reported lower rates of missed care, higher job satisfaction, and a more favorable safety climate than those in "poor" or "mixed" environments. Key factors associated with increased missed care included insufficient staffing, inadequate resources, and limited nurse-physician collaboration. Supportive leadership and resource availability were found to enhance both job satisfaction and safety climate perceptions. Conclusion: The findings underscore the importance of improving organizational factors within nursing work environments to reduce missed care and enhance job satisfaction and safety climate. Hospital administrators should prioritize supportive leadership, adequate staffing, and resources, which may lead to better patient outcomes and improved well-being among nursing staff.